Neotpravlennoe pisʹmo [videorecording (DVD)] - Iordanova, Dina (Criterion collection, 2012)
This absorbing tale of exploration and survival concerns four members of a geological expedition who are stranded in the bleak and unforgiving Siberian wilderness while on a mission to find diamonds.